Audit Sistem Informasi Akademik Menggunakan Framework COBIT 5 di STMIK Kaputama Binjai - Dea Puspita; Damai Aulia Br Karo; Ronauli Silaban; Noval Ramadana (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
The use of information technology in education has become common, including in universities such as STMIK Kaputama Binjai. The Academic Information System (AIS) is an important component in college operations, assisting in the management of student data, lecturers, grades, and other academic information. However, it is important to conduct an AIS IT governance audit to evaluate the effectiveness and efficiency of the system. In this context, the audit was conducted using the COBIT 5 framework, focusing on the MEA (Monitor, Evaluate & Access) domain. The results of this audit provide recommendations to improve maturity levels in various COBIT 5 domains, such as improving the responsiveness of IT support services and setting clear KPIs for system performance evaluation. Thus, this audit is expected to be the basis for improving AIS IT governance at STMIK Kaputama Binjai in order to support the teaching and learning process more effectively and efficiently.